Speech acts in Indonesian High School EFL textbooks: Representation & learning implications - Sudartini, Siti; Sutrisno, Adi; Roselani, Ni Gusti Ayu (Jurnal Kependidikan: Penelitian Inovasi Pembelajaran, 2024)
This study is to analyse the representation and characteristics of speech acts in Indonesian high school EFL textbooks, with two focuses: 1) the representation of speech acts; and 2) the characteristics of their presentation. Using qualitative method and critical discourse analysis, the data were taken from the textbooks of grade X by Widiati, U., Rohmah, Z., & Furidah (2017; 2018) and grade XI by Bashir (2017). The researcher acted as an instrument, using qualitative descriptive analysis. The results of this study are as follows. First, the presentation of speech acts already exists in the textbooks, but it is inadequate, because there are only four: assertive, directive, commissive, expressive, while there is no declarative type. In addition, the representation is also less varied. Second, the characteristics of speech acts presentation are adequate to facilitate understanding for students in developing their English competence. The speech acts are presented in the form of speaking skill materials and dialogue examples. This study underlines the need to improve the representation and presentation of functional speech acts in Indonesian high school EFL education.